The electrochemical behavior of Mg–9Al–0.5Zn, Mg–9Al–0.7Zn, and Mg–9Al–1.0Zn in a NaCl solution. Issue 11 (31st May 2019) - Zhao, Xinyue; Su, Jinhao; Li, Guangyu; He, Jinmeng; Chen, Shixing; Wang, Guixiang; Liu, Aidong
Abstract: In this study, the electrochemical behavior of Mg–9Al–0.5Zn, Mg–9Al–0.7Zn, and Mg–9Al–1.0Zn electrodes in a 0.7 mol L −1 NaCl solution is evaluated by using potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), scanning electron microscopy (SEM), and potentiostatic oxidation. The utilization efficiencies of these materials are also determined. The results show that the Mg–9Al–1.0Zn alloy has the highest corrosion resistance and that Mg–9Al–0.5Zn displays the largest discharge current in the 0.7 mol L −1 NaCl solution at 25°C. In addition, the utilization efficiencies of the alloys decrease as follows: Mg–9Al–1.0Zn > Mg–9Al–0.7Zn > Mg–9Al–0.5Zn. This study illustrates that doping Zn into Mg‐Al electrodes increases the corrosion resistance and utilization efficiency but decreases the discharge activity of Mg–Al–Zn anodes when the Zn content is between 0.5% and 1.0%. Abstract : The Mg–9Al–0.5Zn, Mg–9Al–0.7Zn and Mg–9Al–1.0Zn discharge in a 0.7 mol L −1 NaCl electrolyte solution at room temperature. The addition of Zn increases the utilization efficiency and corrosion resistance, but decreases the discharge activity of Mg–Al–Zn electrodes when Zn content is between 0.5% and 1.0%.